Progestin-Primed Ovarian Stimulation Protocol for Patients in Assisted Reproductive Technology: A Meta-Analysis of Randomized Controlled Trials - Guan, Shaogen; Feng, Yuezhi; Huang, Yonghan; Huang, Jia (Frontiers in Endocrinology, 2021)
Objectives Progestin-primed ovarian stimulation (PPOS) is a new ovarian stimulation protocol that can block the luteinizing hormone (LH) surge through progesterone instead of traditional down regulating or gonadotropin-releasing hormone (GnRH) antagonist, and in order to achieve multi-follicle recruitment. This paper aims to investigate the effectiveness of PPOS and its suitability for infertile patients with different ovarian reserve functions. Methods We searched published randomized controlled trials (RCTs) about PPOS on Cochrane Library, PubMed, Embase, and Web of Science. The search period spanned from January 1, 2015 to November 16, 2020. The data were extracted, and the meta-analysis was performed on ovarian stimulation as well as embryological and clinical outcomes. The outcomes were pooled by a random effects model, and the risk of heterogeneity was evaluated. Subgroup analysis was performed for different ovarian reserve patients. Results The clinical pregnancy rates and live birth or ongoing pregnancy rates with the PPOS protocol were not different from those with the control group. In the diminished ovarian reserve (DOR) subgroup, the PPOS protocol had a lower rate of premature LH surge [RR = 0.03, 95% CI = 0.01 to 0.13, p < 0.001]. The PPOS protocol had a lower rate of ovarian hyperstimulation syndrome (OHSS) [RR = 0.52, 95% CI = 0.36 to 0.76, p < 0.001, I2 = 0.00%]. The secondary outcomes showed that the number of oocytes retrieved, MII oocytes, and viable embryos was higher than that of the control protocol in DOR patients [(MD = 0.33, 95% CI = 0.30 to 0.36, p < 0.001), (MD = 0.30, 95% CI = 0.27 to 0.33, p < 0.001), (MD = 0.21, 95% CI = 0.18 to 0.24, p < 0.001)] and normal ovarian reserve (NOR) patients [(MD = 1.41, 95% CI = 0.03 to 2.78, p < 0.001), (MD = 1.19, 95% CI = 0.04 to 2.35, p < 0.001), (MD = 1.01, 95% CI = 0.21 to 1.81, p = 0.01)]. Conclusion The findings suggest that PPOS is an effective ovarian stimulation protocol and is beneficial for patients with different ovarian reserve functions, which needs to be validated in more RCTs with larger samples.